HOW EFFECTIVE IS INDONESIA'S STRATEGIC HEDGING APPROACH? - Hartanto, Yusa Adi (Jurnal Pertahanan dan Bela Negara, 2025)
The intensifying strategic rivalry between the United States and China has significant implications for regional stability, compelling Indonesia to navigate increasingly complex geopolitical dynamics. Maintaining balanced relations with both major powers while safeguarding national sovereignty is central to Indonesia’s foreign policy, which is anchored in the principle of being “free and active.” Within this framework, strategic hedging has emerged as a key approach. This study critically examines the effectiveness of Indonesia’s hedging strategy and explores potential adaptations to address future challenges. Using a qualitative methodology, the research evaluates Indonesia’s strategic posture through two case studies: (1) its position on Indo-Pacific order-building initiatives, and (2) its response to territorial disputes in the South China Sea. These cases provide empirical insights into Indonesia’s strategic hedging approach’s strengths and limitations. The findings indicate that Indonesia has primarily implemented hedging effectively, balancing the risks of entrapment, polarization, and security threats while maintaining strategic autonomy. Nonetheless, persistent external pressures, particularly China’s assertiveness, highlight the need for Indonesia to strengthen its policy framework. To ensure long-term strategic resilience, the study recommends enhancing defense capabilities by developing a more self-reliant domestic defense industry and pursuing a more integrated security strategy that reduces dependence on foreign powers. This research acknowledges certain limitations, particularly the subjectivity inherent in qualitative analysis when assessing complex strategic behaviors. Additionally, the conceptual framework may not fully account for the non-linear nature of hedging or the influence of domestic political, economic, and institutional factors. In conclusion, while Indonesia’s current hedging strategy remains relevant, reinforcing self-reliance and advancing a more cohesive national security approach will be essential for navigating the evolving geopolitical landscape.